Rapid synthesis of highly monodispersed silver nanoparticles from the leaves of Salvadora persica - Khan, Mamatha R. Shadab; Salunkhe, Pooja; Satpute, Shruti; Kendurkar, Shuchishweta; Prabhune, Asmita; Deval, Animesh; Chaudhari, Bhushan P. (Materials Letters, 2017)
We have demonstrated a one pot green protocol for the synthesis of highly monodispersed silver nanoparticles using leaves of Salvadora persica plant. When the leaf extract of Salvadora persica plant reacted with silver nitrate (AgNO3) solution it resulted in the synthesis of highly monodispersed silver nanoparticles with an average size of 3 nm. These nanoparticles were then completely characterized by UV-Visible spectroscopy, Transmission Electron Microscopy, Energy Dispersive Analysis of X-Rays, X-ray diffraction analysis and Fourier Transform Infrared analysis. (C) 2017 Elsevier B.V. All rights reserved.

Robust optimization and characterization of MCM-41 nanoparticle synthesis using modified sol-gel method - Shende, Rajnigandha A.; Chaudhari, Bhushan P. (ChemistrySelect, 2023)
Mesoporous silica nanoparticles (MSN) for drug delivery application requires great expertise to synthesize small sized monodisperse particles. We aimed at synthesizing and optimizing MCM-41 particles with the modified Stober's method by adjusting factors such as concentrations of cetyltrimethylammonium bromide (CTAB), sodium hydroxide (NaOH) and water (H2O) with respect to tetraethyl orthosilicate (TEOS), and a process parameter (stirring). We comprehended that the reactants determined the shape and size of both the particles and pores. Upon extensive characterization we report the synthesis of spherical particles of similar to 70 nm size in a monodisperse population; the structures had hexagonal ordered pores of diameter 3.071 nm and volume 3.124 cm(3)/g; the total surface area of 3410.648 m(2)/g of the particles was covered with silanol groups that aid in functionalization; the particles exhibited great thermal stability. Thus, the extensive optimization fabricated robust MCM-41 particles fit for drug delivery application.
Keywords: characterization technique; dynamic light scattering (DLS); mesoporous materials; Nanoparticles; sol gel processes